Customer Relationship Building as a Success Factor - Karolina Fij alkowska; Joanna Lisok (Communications of International Proceedings, 2022)
The publication cites information on the essence of building customer relationships, or the essence of partnership marketing. Analyzing current trends and needs of today's businesses, the topic of establishing and maintaining relationships with customers is nowadays crucial for companies to achieve their goals. The publication is based on a literature study and the analysis of data obtained from a certain enterprise. Conclusions that can be drawn from the publication can be summarized as follows-companies that strive to obtain and maintain proper relationships build a strong and, above all, stable competitive advantage on the market.
Keywords: relationship marketing; partner marketing; customer loyalty; customer relations in times of pandemic; customer; with the customer in the era of pandemics; consumer behavior; customer; satisfying consumer needs; building relationships with the customer; building competitive advantage; stable market position